Information Spillovers at Earnings Announcements - FRANKEL, RICHARD; GODIGBE, BRIGHT GERSHION; RABIER, MARYJANE (Journal of Accounting Research, 2025)
ABSTRACT Research documents price co‐movements, or “spillovers,” between focal firms and their peers at focal firms’ earnings announcements. We find that both signed and absolute co‐movements between focal‐ and peer‐firm returns are significantly lower at earnings‐announcement dates compared to other dates. Analytically, we demonstrate that co‐movements do not necessarily indicate common information; instead, co‐movements measure the relative proportion of focal firm‐specific information to common information in focal‐firm earnings announcements. We study three settings where information transfers might be higher: when focal firms report significant earnings surprises, are industry leaders, or share correlated earnings patterns with peer firms. We continue to find lower return correlations during focal‐firm earnings announcements. We conduct two alternative tests but fail to find evidence that common information released during focal‐firm earnings announcements is significantly greater than on other days. These results raise doubt about the extent of the information externality attributable to financial‐report releases.